ANALISIS LITERASI INFORMASI MAHASISWA UNIVERSITAS WARMADEWA - Kadek Lianna Sri Wahyuni; I Putu Suhartika; Ni Putu Premierita Haryanti (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2025)
The aim of this study is to analyze the information literacy of students at Warmadewa University using the Seven Pillars of Information Literacy model. This research employs a qualitative method with a descriptive approach. Data collection techniques include interviews, observations, and documentation involving active students and librarians within the Warmadewa University environment. The Seven Pillars model is used to assess students' abilities across seven key aspects of information literacy: Identify, Scope, Plan, Gather, Evaluate, Manage, and Present. Based on the findings, it was revealed that Warmadewa University students possess relatively good skills in several pillars of information literacy, particularly in the aspects of Identify, Scope, Gather, and Present. However, their ability to evaluate the credibility of sources (Evaluate) and to systematically manage information (Manage) still needs improvement. Supporting factors identified include the availability of digital library facilities, online catalogs, and guidance from librarians. On the other hand, the lack of structured information literacy programs and limited specialized training are the main obstacles. It is recommended that the library and educational institutions take a more active role in developing sustainable and relevant information literacy programs tailored to students' needs.